Analisis Fasilitas Kantor dan Disiplin Kerja terhadap Kinerja Pegawai Bagian Pengadaan Barang dan Jasa Sekretariat Daerah Kabupaten Buru Selatan - ASTIKA, STEPI W.; SAHETAPY, P. (Patria Artha University, 2022)
This study aims to determine the magnitude of the influence of internal communication consisting of vertical communication and horizontal communication both simultaneously and partially on the effectiveness of the work at the Procurement Section of the Regional Secretariat of South Buru Regency, as well as identify obstacles in carrying out internal communication in the Procurement Section of Goods and Services. Regional Secretariat of South Buru Regency. This research is descriptive by using a quantitative approach so that to support this research activity, the main data collection is carried out by means of a questionnaire. The data analysis of this research used descriptive analysis and multiple linear regression. Based on the results of the analysis, it is known that the Vertical Communication and Horizontal Communication simultaneously or simultaneously have a significant effect on the Work Effectiveness of employees. Partially, only vertical communication has a significant effect on employee work effectiveness, while horizontal communication does not have a significant effect. Barriers to internal communication in the Procurement Section of the Regional Secretariat of South Buru Regency include: technical barriers, semantic barriers, and human barriers.